2012
DOI: 10.1007/s11605-011-1704-6
|View full text |Cite
|
Sign up to set email alerts
|

Superior Prognostic Importance of Perineural Invasion vs. Lymph Node Involvement After Curative Resection of Duodenal Adenocarcinoma

Abstract: Perineural invasion is a stronger predictor for recurrence and survival than tumor size, depth of infiltration, lymph node involvement, and type of resection in patients with duodenal adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 30 publications
4
38
0
Order By: Relevance
“…Morbidity and mortality rates associated with surgical treatment for resectable duodenal cancer are high. Reported morbidity rates are around 40 per cent, and mortality rates range between 0 and 8·5 per cent ( Table S3 , supporting information).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morbidity and mortality rates associated with surgical treatment for resectable duodenal cancer are high. Reported morbidity rates are around 40 per cent, and mortality rates range between 0 and 8·5 per cent ( Table S3 , supporting information).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection offers the only chance of cure. There are few published studies on outcomes after surgery owing to the rarity of this condition. These studies are characterized by a limited number of patients and long study periods, resulting in conflicting reported outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, given the low prevalence of this disease in the general population and the limited number of clinical studies, there is no consensus as to the most effective treatment strategy. Conflicting information exists on the required extent of resection of duodenal adenocarcinoma [3, 4]. Some have suggested pancreaticoduodenectomy for all duodenal adenocarcinoma patients, regardless of TNM (tumor-node-metastasis) stage and location, to ensure that there is a tumor-free (R0) margin and adequate regional lymphadenectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Others have advocated the use of segmental resection for appropriate patients [3]. In the last decade, different studies have evaluated the correlations between clinical, pathological, and treatment variables in order to identify specific prognostic factors associated with survival [49]. Identifying the prognostic factors is of great significance for the comprehensive understanding of the characteristics of this disease and has an important guiding meaning for the disease prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Both perineural infiltration and lymphovascular invasion in pancreaticoduodenectomy specimens were found to be associated with a decreased 5-year survival [1]. Perineural invasion alone has also been shown to be a strong predictor of survival in patients with periampullary, duodenal, and ampullary adenocarcinomas [24]. Talamini et al identified a higher resectability rate and better prognosis in patients with ampulla of Vater tumors and emphasized that the LN status likely influenced survival outcomes [5].…”
Section: Introductionmentioning
confidence: 99%